2014
DOI: 10.1371/journal.pone.0085757
|View full text |Cite
|
Sign up to set email alerts
|

Expression Variants of the Lipogenic AGPAT6 Gene Affect Diverse Milk Composition Phenotypes in Bos taurus

Abstract: Milk is composed of a complex mixture of lipids, proteins, carbohydrates and various vitamins and minerals as a source of nutrition for young mammals. The composition of milk varies between individuals, with lipid composition in particular being highly heritable. Recent reports have highlighted a region of bovine chromosome 27 harbouring variants affecting milk fat percentage and fatty acid content. We aimed to further investigate this locus in two independent cattle populations, consisting of a Holstein-Fries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 40 publications
5
84
1
Order By: Relevance
“…t7:20 † Significance was declared if P-value was ≤ 0.005 after applying Bonferroni adjustment (0.05 divided by the number of comparisons that was 10).possible that one of the main functions of AGPAT6 might be phospholipid biosynthesis for milk fat globule membranes. This claim is supported by recent determinations of AGPAT6 as a candidate gene for milk fat percentage QTL in dairy cattle[28,52]. In our study, however, there were no significant association between AGPAT6 polymorphisms and milk fat percentage.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…t7:20 † Significance was declared if P-value was ≤ 0.005 after applying Bonferroni adjustment (0.05 divided by the number of comparisons that was 10).possible that one of the main functions of AGPAT6 might be phospholipid biosynthesis for milk fat globule membranes. This claim is supported by recent determinations of AGPAT6 as a candidate gene for milk fat percentage QTL in dairy cattle[28,52]. In our study, however, there were no significant association between AGPAT6 polymorphisms and milk fat percentage.…”
supporting
confidence: 88%
“…suggested that genetically these phenotypes can be considered as the 460 same trait [16]. Polymorphisms in AGPAT6 were also associated with 461 milk plamitic acid concentration [28]. There were no significant associ-462 ations between AGPAT6 haplotypes and milk FA composition deter-463 mined in our study.…”
mentioning
confidence: 58%
“…Both DGAT1 and AGPAT6 are key components of the overall pathway leading to synthesis of milk lipid droplets and affect milk fat yield and composition. 42 , 41 , 33 Although the expression of AGPAT6 did not change, the fact that overexpression of miR-26a/b and their host genes had a significant effect on DGAT1 mRNA expression provides evidence of a mechanistic link between the miRNA and the process of desaturation and esterification…”
Section: Discussionmentioning
confidence: 99%
“…The transcription rate of GPAT4 is highly correlated with concentrations of diacylglycerols and triacylglycerols in milk [9,15]. In a more recent study, this region on chromosome 27 was reported for associations with milk fat and milk volume, protein and lactose content in Holstein and Jersey crossbreds [92]. Mullen et al [110] have detected several novel and previously identified associations involving variants within introns of the IGF1 gene associated with milk protein yield, milk fat yield, milk fat concentration, somatic cell score and carcass associated traits in Holstein dairy cattle [110].…”
Section: Candidate Genes Identified In the Key Tissues Through Associmentioning
confidence: 96%